PENINGKATAN MOTIVASI BELAJAR AL-QUR’AN DENGAN PENDEKATAN NAGHAM DI SDIT MIFTAHUL ULUM CINERE, DEPOK, JAWA BARAT - Samsul Bahri Tanrere; Mu’azir Mustaqim Bunis (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2022)
This paper discusses the application of Al-Qur’an learning with the nagham approach at SDIT Miftahul Ulum Cinere Depok, West Java. The focus of this paper is to investigate the increase in motivation to learn the Koran with the nagham approach. This nagham approach is an effort to increase motivation to learn Al-Qur’an in schools which leads to an active, effective and fun learning process. The research method in this paper uses a qualitative research type using descriptive analysis. Methods of data collection using interview techniques, documentation, and observation. Data analysis uses data reduction, data presentation, and data conclusion drawing. Checking the validity of the data using data poleulation. This paper shows that learning the Quran with the nagham approach at SDIT Miftahul Ulum Cinere Depok, West Java, can increase students' motivation to learn Al-Qur’an. This can be seen from the active, creative, and fun learning process. In increasing the motivation to learn the Koran with the nagham approach. The school focuses on three things, namely professional educators and education, good and adequate facilities and infrastructure and a longer duration of Al-Qur’an learning hours. Thus learning the Koran with the nagham approach at SDIT Miftahul Ulum Cinere Depok West Java can increase students' motivation to learn Al-Qur’an and lead to an active, effective and fun learning process